Motivasi Siswa Terhadap Kegiatan Pengembangan Diri Seni Tari di SMP Negeri 28 Kecamatan Kuranji Padang - Anggraini Anggraini; Susmiarti Susmiarti; Afifah Asriati (FBS Universitas Negeri Padang, 2015)
Abstract This article aims to explain the students' motivation in participating in the activities of self-development of dance in Junior High School 28 Kecamatan Kuranji Padang. This type of research is qualitative and descriptive method. The object of this research is in the seventh grade students of SMPN 28 Kecamatan Kuranji Padang. Which followed the self-development activities amounted to 40 students. The data collection techniques, observation, interviews and documentation. Data analysis was performed with a qualitative approach model of Miles and Huberman. The results showed that from forty 40 students who participated in the self-development of dance, and 30 students who are not motivated, due to the lack of student motivation in training he bersunguh- not really, and a lot of joking in training only 10 righteous - properly motivated towards self-development activities of the art of dance. It can be concluded that the students have the motivation to dance. Most of the students who follow the development of the art of dance expressed themselves motivated to dance. Keywords: motivation, self-development, the art of dance.